Malaysian legal system: sources of law and the Malaysian courts - Daud, Mahyuddin (2019)
Malaysia is a multi-ethnic, multicultural and multi-religious country The national legal system reflects such heterogeneous society which has been influenced and shaped by external and individual cultures Malaysia has a plural legal system, a national legal system within which coexist two or more legal traditions (heritage of common legal concepts, methodology, institutions, processes, and remedies). MLS is based on common law tradition Common law and rules of equity of England were received together with British administration when British came to the Malay Peninsula, first to Penang in 1786 The British occupation of Penang, Singapore and Melaka – which together became a British colony known as the Straits Settlements – was followed by British intervention and indirect rule through the treaties of protection in the Malay states, beginning with Perak in 1874. In Borneo, north Borneo (now Sabah) and Sarawak became British protectorates in 1888 and British colonies in 1946, after being privately administered by the British North Borneo Company and the ‘White Rajahs’ The territories of the Sultans of Brunei and Sulu were ceded to Western adventurers.